(untitled) (Research, Society and Development, 2020)
Correction of soils is a required practice that aims to reduce the harmful effects of soil acidity, promote better development of the plants and ensure the productive potential of agriculture. In this sense, the objective of this work was to evaluate the maize yield in monoculture and / or intercropped and to study the development of Urochloa spp roots according to different combinations of chemical correction of the soil in rainfed conditions. The experiment was developed in an experimental area, Selvíria, MS, Brazil in dystrophic Oxisol. The experimental design used was the randomized blocks with subplots, with three replications. The soil correction treatments were arranged in the plots (control, gypsum, lime (0 - 0.2 m); lime and gypsum (0 - 0.2 m); lime (0 - 0.4 m); lime and gypsum (0 - 0.4 m)), and the subplots were occupied with maize, maize intercropped with U. ruziziensis or with Mulato II hybrid (Convert HD 364) The two intercrop with forages produced sufficient amounts of straw to start and/or maintain no-tillage system in the Cerrado region and the presence of forage in maize crop did not influence grain yield. The Mulato II hybrid had a larger root diameter, being more indicated for compacted soils, however longest root lengths were obtained by U. ruziziensis.